Pemanfaatan Situs Pura Taman Sari di Banjar Sengguhan, Semarapura Kangin, Klungkung Sebagai Daya Tarik Wisata - Trisna Amelia, Ni Putu Ari; Srijaya, I Wayan; Wardi, I Nyoman (Humanis, 2017)
Taman Sari Temple has been builded around in 1710, this temple has been designated as a cultural heritage in Klungkung regency. Taman Sari Temple of the kingdom of Klungkung, existing structures on the site he has the remains of a building of which the meru tumpang sebelas, meru tumpang sembilan and ancient statues. This study aims to determine the potential that can be exploited as a tourist attraction and what efforts need to be made in the utilization of the site as a tourist attraction. This study used a structural functional theory and this study used data collection techniques are observation, literature study and interviews. Data analysis techniques used, is a qualitative analysis, quantitative analysis and SWOT analysis. Based on the results of data processing and data analysis in this study provides an overview of the potential that exists in the Taman Sari Temple, and efforts to use public perception needs to be done to make this site as a tourist attraction. There is potential for tangible and intangible form of two buildings meru, namely tumpang sebelas dan meru tumpang sembilan, ancient statues, pools and other support buildings and accompanied by the supporting factors around the site which has become a leading tourist attraction in Klungkung regency. Efforts should be made to make the temple as a tourist attraction, such a improving human resources, additional facilities, and infrastructure, dissemination of information, as well as structuring site conservation efforts.
Keywords: Taman Sari Temple, potential, utilization, tourist attraction